Development of a Spatiotemporal Data Model for Management and Visualization of Surface Movement Data - Mohd Rahim, Mohd Shafry (2008)
Spatiotemporal data is a part of geographical data required in Geographical Information System (GIS). Generally, the existing GIS are not suited to manage changes occurring in the data with time. The capability of managing geographic data with time depends on the underlying data model in which the data model has to take into account the spatiotemporal aspects of the geographic data. Thus, a Spatiotemporal Data Model is required to manage changes in GIS data. Spatiotemporal Data Model represents the abstraction of data management in GIS. Surface movement on three dimensional objects is one of the spatiotemporal data which represents changes of the surface taking place in geographic phenomena. However, current Spatiotemporal Data Model and current GIS software are not adequate for managing the surface movement of three dimensional objects while representing the data. Most of the existing data models brought us to the conclusion that a new Spatiotemporal Data Model is needed to improve the management of three dimensional data with temporal element. Therefore, a new Spatiotemporal Data Model, Surface Movement Spatiotemporal (SMST) Data Model is proposed, which supports the management and visualization of surface movement data in three dimensional objects such as terrain model. The data model were developed under consideration of real world events together with current data collection, for example, a terrain model in the geographic phenomena which deals with changes from time to time based on natural phenomena and human activity. The data were collected by capturing images from time to time. Formalization of the surface movement reconstruction is a fundamental knowledge to develop the SMST Data Model. Currently, in many fields, surface reconstruction does not consider the temporal element. Therefore, the surface movement of three dimensional objects is formalized by enhancing the surface reconstruction method; that is by integrating it with temporal element. In order to test and evaluate the SMST Data Model, a database management system with a loading and a retrieval algorithm suitable to this model were developed. The retrieved data from the database system is saved in the proposed data format for surface movement visualization. In developing the visualization tool, visualization algorithm was used by employing the morphing technique which uses parametric equation. The proposed model was tested using digital terrain model digitized from a series of aerial photos. The model can store and manage surface movement data while reducing the redundancy of data in the database system. Percentage of reduced data redundancy is based on the number of points involved in the movement process. The model stores only the movement points in the surface. Besides, the proposed model can retrieve data for simulating surface movement on the three dimensional object. Therefore, the major contributions of this research are the formalization of surface movement data and the proposed SMST Data Model which can manage surface movement data on three dimensional objects with respect to time.